Carbon nanotubes as a novel drug delivery system for anticancer therapy: a review - Swatantra Kumar Singh Kushwaha; Saurav Ghoshal; Awani Kumar Rai; Satyawan Singh (Universidade de São Paulo, 2013)
Carbon nanotubes (CNTs) were discovered in 1991 and shown to have certain unique physicochemical properties, attracting considerable interest in their application in various fields including drug delivery. The unique properties of CNTs such as ease of cellular uptake, high drug loading, thermal ablation, among others, render them useful for cancer therapy. Cancer is one of the most challenging diseases of modern times because its therapy involves distinguishing normal healthy cells from affected cells. Here, CNTs play a major role because phenomena such as EPR, allow CNTs to distinguish normal cells from affected ones, the Holy Grail in cancer therapy. Considerable work has been done on CNTs as drug delivery systems over the last two decades. However, concerns over certain issues such as biocompatibility and toxicity have been raised and warrant extensive research in this field.